Aerated Irrigation Promotes Soil Respiration and Microorganism Abundance around Tomato Rhizosphere. Issue 5 (1st September 2019) - Zhu, Yan; Cai, Huanjie; Song, Libing; Chen, Hui
Abstract : Core Ideas: Aerated irrigation improved soil aeration, increasing oxygen concentration and air‐filled porosity. Aerated irrigation enhanced soil, microbial, and root respiration and microbe abundance. Soil oxygen, air‐filled porosity correlated with respiration, microbe abundance. Aerated irrigation has economic benefits, promoting fruit yield and IWUE. Aerated irrigation (AI), by which aerated water is supplied to soil through subsurface drip irrigation (SDI), has shown high yield potential and application prospects. This study evaluated the impact of AI on soil aeration, respiration components, and microorganism abundance to determine the relationships between these parameters. Four treatments (W1AI, W2AI, W1CK, and W2CK) combining AI and nonaerated SDI (CK) and two irrigation levels (W1 and W2, with crop‐pan coefficients of 0.6 and 1.0) were conducted in a greenhouse during two tomato ( Lycopersicon esculentum Mill.) growing seasons in April to July in 2015 and 2016. The results showed that AI improved soil aeration conditions, with soil oxygen concentration and air‐filled porosity significantly increasing by 5.86 and 5.16%, respectively, compared with CK. The W1AI treatment increased soil, microbial, and root respiration as well as bacteria, actinomycetes, and fungi abundance by 18.8, 10.0, 23.4, 30.1, 29.4, and 30.1%, respectively, compared with W1CK, and W2AI significantly increased these by 24.2, 15.3, 28.7, 39.2, 39.3, and 37.1%, respectively, compared with W2CK. Moreover, the abundance of bacteria, actinomycetes, and fungi with W2AI significantly increased by 26.9, 27.1, and 24.8%, respectively, compared with W1AI. Soil oxygen concentration (under controlled soil temperature) and air‐filled porosity positively correlated with soil respiration and microorganism abundance. Mean fruit yield with AI was 22.4% higher than CK. Aerated irrigation therefore stimulated soil respiration and microbial proliferation by improving soil aeration conditions. Enhanced soil aeration, respiration, and microorganism abundance under AI provide economic benefit by improving fruit yield.